Thermal Evaluation, Rheological Properties and Characterization of Pristine, Modified and Polyacrylamide-Mediated Grafted Acacia modesta Gum - Hira Munir; Muhammad Shahid; Muhammad Bilal; Hafiz M.N. Iqbal (Journal of Pure and Applied Microbiology, 2020)
Naturally occurring plant-based gums are being widely used in different industries due to their unique thickening and gelling potentialities. The research was planned to evaluate the influence of hydrolysis and modification on rheological and thermal properties of Acacia modesta (Phulai) gum extracts. The gum was hydrolyzed and modified by different chemical methods including polyacrylamide grafting, carboxymethylation, acidic and basic hydrolysis to alter the viscosity behavior. The rheological behavior of selected gum extracts was studied. The change in structure and thermal behavior after processing was determined by Differential scanning calorimetry (DSC), X-ray diffraction (XRD), Thermogravimetric analysis (TGA) and Fourier transforms infrared spectroscopy (FTIR). The analysis of DSC and TGA revealed that the processed gum samples were thermally more stable as compared to pristine counterpart of the crude gum. The present results of A. modesta would be useful for incorporation in various applications in the food and pharmaceutical industries.